The changing face of central banking evolutionary trends since World War II - Siklos, Pierre L. 1955- (Cambridge University Press, 2002)
Central banks have emerged as the key players in national and international policy making. This book explores their evolution since World War II in 20 industrial countries. The study considers the mix of economic, political and institutional forces that have affected central bank behaviour and its relationship with government. The analysis reconciles vastly different views about the role of central banks in the making of economic policies. One finding is that monetary policy is an evolutionary process
Title from publisher's bibliographic system (viewed on 08 Oct 2015)
Keywords: Geschichte 1945-2000; Geschichte; Banks and banking, Central / History; Monetary policy / History; Notenbank; Geldpolitik; Internationaler Vergleich